Sensory evaluation of white asparagus (Asparagus officinalis L.) hybrids - Takácsné Hájos, M.; Rubóczki, T.; Szutor, M. (International Journal of Horticultural Science, 2016)
Comprehensive system of sensory evaluation was developed to obtain information on the different varieties by determining asparagus quality parameters. 9 sensory characteristics were estimated to describe flavour differences. The tests were carried out in 4 varieties of white asparagus (Asparagus officinalis L.) grown on brown humus sand soil by etiolate method in ridge cultivation. The experiment was performed at the University of Debrecen in Debrecen-Pallag. To increase the Hungarian asparagus consumption, a classification of varieties regarding to asparagus flavour is necessary. In our experiment it could be stated that there are strict correlations (0.892) between the sweetness – total impression and between lacks of unpleasant aftertaste – total impression (0.870). The result of surveys can lead to higher popularity of the asparagus. These results are presented in order to recommend the varieties to producers for a successful marketing. The taste of asparagus is mostly influenced by variety, soil type and growing conditions. In our experiment, ‘Vitalim’ hybrid exceeded by several sensory parameters. This hybrid scored 788.38 over 900. The elder population showed more interest in asparagus consumption than younger ones. 50% of the participants are able to pay only 500-600 HUF/kg. It could be realized to ensure the proper growing place, hybrid and direct trade. Marketing and more information is necessary to increase the popularity of this vegetable among the younger generation.